Visual expectation reaction time and attentional control associated with prenatal maternal biomarkers of organophosphate and pyrethroid exposures in a Thai birth cohort - Pimjuta Nimmapirat; Zimeng Ren; Margaret Wolan Sullivan; Wathoosiri Promduang; Nattapon Chaikittipornlert; Tippawan Prapamontol; Warangkana Naksen; Parinya Panuwet; Dana Boyd Barr; Brittney O. Baumert; Pamela Ohman-Strickland; Panrapee Suttiwan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Development of a Pesticide Labeling Literacy Scale for Thai Rice Farmers: Item Generation and Content Validity Testing - Phiranut Saeneewong Na Ayuttaya; Nuttaporn Lawthong; Mark Gregory Robson; Wattasit Siriwong (Journal of Agromedicine, 2025)

Evaluation of three serological tests for the diagnosis of Brucella suis in dogs using Bayesian latent class analysis - Catherine C. Kneipp; Ronald Coilparampil; Mark Westman; Monica Suann; Jennifer Robson; Simon M. Firestone; Richard Malik; Siobhan M. Mor; Mark A. Stevenson; Anke K. Wiethoelter (Preventive Veterinary Medicine, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Effect of children secondhand smoke exposure associated with GABA concentration: Influence from parents who are extremely heavy smokers in urban households - Jadsada Kunno; Panu Pimviriyakul; Titaporn Luangwilai; Saowanee Sematong; Busaba Supawattanabodee; Sathit Kuratong; Mark Gregory Robson (Science of The Total Environment, 2024)

Modelling buoyancy-driven vertical movement of Trichodesmium application in the Great Barrier Reef - Chinenye J. Ani; Mark Baird; Barbara Robson (Ecological Modelling, 2024)

Pesticide Safety Behavior among Cocoa Farmers in Nigeria: Current Trends and Determinants - Oluseye O. Oludoye; Wattasit Siriwong; Mark G. Robson (Journal of Agromedicine, 2023)

eReefs modelling suggests Trichodesmium may be a major nitrogen source in the Great Barrier Reef - Chinenye J. Ani; Scott G. Smithers; Stephen Lewis; Mark Baird; Barbara Robson (Estuarine, Coastal and Shelf Science, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Rotational horse grazing and dry weather maximize infiltration into soil macropores - Laura B. Kenny; Daniel Giménez; Joshua S. Caplan; Ali Al-Sarraji; Mohson AlHello; Mark G. Robson; William Meyer; Carey A. Williams (Soil and Tillage Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Using urine as a biomarker in human exposure risk associated with arsenic and other heavy metals contaminating drinking groundwater in intensively agricultural areas of Thailand - Pokkate Wongsasuluk; Srilert Chotpantarat; Wattasit Siriwong; Mark Robson (Environmental Geochemistry and Health, 2018)

Modeling What We Sample and Sampling What We Model: Challenges for Zooplankton Model Assessment - Jason D. Everett; Mark E. Baird; Pearse Buchanan; Cathy Bulman; Claire Davies; Ryan Downie; Chris Griffiths; Ryan Heneghan; Rudy J. Kloser; Leonardo Laiolo; Ana Lara-Lopez; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2017)

Lysophosphatidic acid generation by pulmonary NKT cell ENPP-2/autotaxin exacerbates hyperoxic lung injury - Martina Nowak-Machen; Martin Lange; Mark Exley; Sherry Wu; Anny Usheva; Simon C. Robson (Purinergic Signalling, 2015)

Organophosphate Pesticide Exposure in School-Aged Children Living in Rice and Aquacultural Farming Regions of Thailand - Juthasiri Rohitrattana; Wattasit Siriwong; Tanasorn Tunsaringkarn; Parinya Panuwet; P. Barry Ryan; Dana Boyd Barr; Mark G. Robson; Nancy Fiedler (Journal of Agromedicine, 2014)

Mosaic partial deletion of the PTEN gene in a patient with Cowden syndrome - Erin E. Salo-Mullen; Jinru Shia; Isaac Brownell; Peter Allen; Monica Girotra; Mark E. Robson; Kenneth Offit; Jose G. Guillem; Arnold J. Markowitz; Zsofia K. Stadler (Familial Cancer, 2014)

Health Risk Assessment Related to Dermal Exposure of Chlorpyrifos: A Case Study of Rice Growing Farmers in Nakhon Nayok Province, Central Thailand - Sattamat Lappharat; Wattasit Siriwong; Nutta Taneepanichskul; Marija Borjan; Héctor Maldonado Perez; Mark Robson (Journal of Agromedicine, 2014)

Pesticides Use and Human Health Effects in Agricultural Farmworkers in the Kingdom of Thailand: Current Situation and Concerns - Wattasit Siriwong; Mark Robson (Journal of Agromedicine, 2014)

Contamination and Footprints of Organ‐ophosphate Pesticide on Rice-Growing Farmers’ Bodies: A Case Study in Nakhon Nayok Province, Central Thailand - Sattamat Lappharat; Wattasit Siriwong; Saowanee Norkeaw; Nutta Taneepanichskul; Mark Robson (Journal of Agromedicine, 2014)

Heavy metal contamination and human health risk assessment in drinking water from shallow groundwater wells in an agricultural area in Ubon Ratchathani province, Thailand - Pokkate Wongsasuluk; Srilert Chotpantarat; Wattasit Siriwong; Mark Robson (Environmental Geochemistry and Health, 2014)

The roles of mosquito and bird communities on the prevalence of West Nile virus in urban wetland and residential habitats - Brian J. Johnson; Kristin Munafo; Laura Shappell; Nellie Tsipoura; Mark Robson; Joan Ehrenfeld; Michael V. K. Sukhdeo (Urban Ecosystems, 2012)

Hepatic Metallothionein and Glutathione-S-Transferase Responses in Two Populations of Rice Frogs, Fejervarya limnocharis, Naturally Exposed to Different Environmental Cadmium Levels - Mohd Sham Othman; Wichase Khonsue; Jirarach Kitana; Kumthorn Thirakhupt; Mark Robson; Marija Borjan; Noppadon Kitana (Bulletin of Environmental Contamination and Toxicology, 2012)

Pesticides and Other Chemicals: Minimizing Worker Exposures - Matthew Keifer; Frank Gasperini; Mark Robson (Journal of Agromedicine, 2010)

Cadmium Accumulation in Two Populations of Rice Frogs (Fejervarya limnocharis) Naturally Exposed to Different Environmental Cadmium Levels - Mohd Sham Othman; Wichase Khonsue; Jirarach Kitana; Kumthorn Thirakhupt; Mark Gregory Robson; Noppadon Kitana (Bulletin of Environmental Contamination and Toxicology, 2009)

Analytical Method Developed for Measurement of Dialkylphosphate Metabolites in Urine Collected from Children Non-Occupationally Exposed to Organophosphate Pesticides in an Agricultural Community in Thailand - Chidhathai Petchuay; Somkiet Thoumsang; Parichart Visuthismajarn; Banjong Vitayavirasak; Brian Buckley; Paromita Hore; Marija Borjan; Mark Robson (Bulletin of Environmental Contamination and Toxicology, 2008)

Method of calculating tsunami travel times in the Andaman Sea region - Monte Kietpawpan; Parichart Visuthismajarn; Charlchai Tanavud; Mark G. Robson (Natural Hazards, 2008)

High Sensitivity Differential Scanning Calorimetry Study of DNA-Cationic Liposome Complexes - Mark Saunders; Kevin M. G. Taylor; Duncan Q. M. Craig; Karen Palin; Hazel Robson (Pharmaceutical Research, 2007)

Decoupling the direct and indirect effects of nitrogen deposition on ecosystem function - Pete Manning; John E. Newington; Helen R. Robson; Mark Saunders; Till Eggers; Mark A. Bradford; Richard D. Bardgett; Michael Bonkowski; Richard J. Ellis; Alan C. Gange; Susan J. Grayston; Ellen Kandeler; et al. (Ecology Letters, 2006)
Elevated nitrogen (N) inputs into terrestrial ecosystems are causing major changes to the composition and functioning of ecosystems. Understanding these changes is challenging because there are complex interactions between ‘direct’ effects of N on plant physiology and soil biogeochemistry, and ‘indirect’ effects caused by changes in plant species composition. By planting high N and low N plant community compositions into high and low N deposition model terrestrial ecosystems we experimentally decoupled direct and indirect effects and quantified their contribution to changes in carbon, N and water cycling. Our results show that direct effects on plant growth dominate ecosystem response to N deposition, although long‐term carbon storage is reduced under high N plant‐species composition. These findings suggest that direct effects of N deposition on ecosystem function could be relatively strong in comparison with the indirect effects of plant community change.

The TP53 mutational spectrum and frequency of CHEK2*1100delC in Li–Fraumeni-like kindreds - Rina Siddiqui; Kenan Onel; Flavia Facio; Kedoudja Nafa; Louis Robles Diaz; Noah Kauff; Helen Huang; Mark Robson; Nathan Ellis; Kenneth Offit (Familial Cancer, 2005)

The origin and spread of the HFE-C282Y haemochromatosis mutation - S. Distante; K.J.H. Robson; J. Graham-Campbell; A. Arnaiz-Villena; P. Brissot; Mark Worwood (Human Genetics, 2004)

Hereditary ovarian cancer in Ashkenazi Jews - Luis Robles-daz; Deborah J Goldfrank; Noah D Kauff; Mark Robson; Kenneth Offit (Familial Cancer, 2004)